2006
DOI: 10.1080/01140671.2006.9514396
|View full text |Cite
|
Sign up to set email alerts
|

Responses of New Zealand flower thrips(Thrips obscuratus)to synthetic and natural stimuli (odour and colour) in a wind tunnel

Abstract: The flight responses of female New Zealand flower thrips (Thrips obscuratus, Thysanoptera: Thripidae) to colour (white plastic container), odour (ethyl nicotinate), and to a white Gardenia flower were examined in a wind tunnel with an average airspeed of 0.12m/s. In the absence of odour, the main response of thrips to the white plastic colour cue was increased flight overall and an increase in upwind flight in the direction of that cue. The main response to the synthetic ethyl nicotinate odour was a reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
1
13
2
Order By: Relevance
“…Teulon et al (1999) observed fewer WFT females flew in a flight chamber in the presence of 0.5 ml of para-anisaldhyde (36% flew) than with no cue (70% flew) or only a visual cue (66%). Berry et al (2006) reported a similar effect (inhibited flight) in Thrips obscuratus with 0.5 ml of ethyl nicotinate in the same flight chamber used in the current study. In the present study, there was generally no measureable response of WFT females towards 0.5 ml of para-anisaldehyde.…”
Section: Comparison Of Airflow Ratessupporting
confidence: 71%
See 3 more Smart Citations
“…Teulon et al (1999) observed fewer WFT females flew in a flight chamber in the presence of 0.5 ml of para-anisaldhyde (36% flew) than with no cue (70% flew) or only a visual cue (66%). Berry et al (2006) reported a similar effect (inhibited flight) in Thrips obscuratus with 0.5 ml of ethyl nicotinate in the same flight chamber used in the current study. In the present study, there was generally no measureable response of WFT females towards 0.5 ml of para-anisaldehyde.…”
Section: Comparison Of Airflow Ratessupporting
confidence: 71%
“…All experiments were conducted in a low speed laminar air flow flight chamber previously described by Berry et al (2006). The flight chamber had a total length of 3 m. Within this, the Perspex (6 mm thick) observation chamber measured 0.58 m wide by 0.55 m in height by 1.7 m in length and was illuminated by five 36 W 84 cool lights alternating with five 36 W 96 true light fluorescent tubes above, but immediately outside, the observation chamber.…”
Section: Flight Chamber Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous thrips trapping trials have looked at using different colours (mainly in water trapping) to increase trap catch, but here it was demonstrated that altering trap design is an effective way to increase catch numbers. There have been various trap designs previously used to trap NZFT (e.g.…”
Section: Discussionmentioning
confidence: 94%